Wireless Communication System - Jawaberh, Ezdehar; Abu-Sarah, Reem; Madieh, Rounza (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2005)
The project discusses the idea of implementing a wireless communication system between two locations, such that it is able to send and receive data( text , voice, and image) wirelessly between two PCs. This can be implemented using various methods like amplitude modulation technique or frequency modulation, in addition , the project aims to build an internal wireless local area networks (LAN) using the wireless card (D-link airplus DWL-120+). The project can be a good replacement for the wired communication system that already exists in the university.
no of pages 124, 18644, هندسة حاسوب 5/2005 , in the store
Keywords: Wireless Communication Systems